1982
DOI: 10.1016/0167-5087(82)90527-0
|View full text |Cite
|
Sign up to set email alerts
|

The preparation of stable and actinide nuclide targets for nuclear measurements

Abstract: Specifications for isotopic targets of both stable and actinide nuclides for nuclear measurements are very varied and individually very stringent. The majority of the targets are required to be of specified isotopic and chemical purity, well characterised and uniformly deposited over a precisely defined area. Mass assay of actinide targets may be requested to an accuracy of + 0.1%, resolutions of <10 KeV FWHM may be requested for infinitely thin alpha sources and the Schmidt and Pleasonton criteria must be met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Targets are an essential component in experimental nuclear science as a source of stationary nuclei, e.g., for atomic and nuclear spectroscopy or nuclear reaction studies [1][2][3]. Generally, targets should be chemically pure, uniform, homogeneous, crack-free over the area of interest, and well adherent to the deposition substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Targets are an essential component in experimental nuclear science as a source of stationary nuclei, e.g., for atomic and nuclear spectroscopy or nuclear reaction studies [1][2][3]. Generally, targets should be chemically pure, uniform, homogeneous, crack-free over the area of interest, and well adherent to the deposition substrate.…”
Section: Introductionmentioning
confidence: 99%
“…According to Glover et al [10] an other requested specification for a sources is an observable resolution of <10 keV FWHM for a single peak. This low value is reached only by the vacuum evaporation technique with 239 Pu peaks [10].…”
Section: Resultsmentioning
confidence: 99%
“…This low value is reached only by the vacuum evaporation technique with 239 Pu peaks [10]. Alpha fine structure from a vacuum sublimed 241 Am source evidences quite a broad peak at 5.48 MeV with 13.8 keV FWHM [11].…”
Section: Resultsmentioning
confidence: 99%
“…A review of literature showed that higher quantities of plutonium were deposited from non-aqueous solvents than from aqueous solvents. Further, a non-aqueous solvent reduces the formation of hydrogen bubbles from electrolysis of water that cause an uneven surface in the deposit [20][21][22][23]. The literature reports production of Pu targets containing 200-400 lg/ cm 2 [24][25][26], with some obtaining loadings as high as 987 lg/ cm 2 [20] using a setup comparable to the one used in this work.…”
Section: Target Preparationmentioning
confidence: 90%